Asymmetric Morita–Baylis–Hillman Reaction: Catalyst Development and Mechanistic Insights Based on Mass Spectrometric Back‐Reaction Screening. Issue 49 (24th October 2016) - Isenegger, Patrick G.; Bächle, Florian; Pfaltz, Andreas
Abstract: An efficient protocol for the evaluation of catalysts for the asymmetric Morita–Baylis–Hillman (MBH) reaction was developed. By mass spectrometric back‐reaction screening of quasi‐enantiomeric MBH products, an efficient bifunctional phosphine catalyst was identified that outperforms literature‐known catalysts in the MBH reaction of methyl acrylate with aldehydes. The close match between the selectivities measured for the forward and back reaction and kinetic measurements provided strong evidence that the aldol step and not the subsequent proton transfer is rate‐ and enantioselectivity‐determining. Abstract : Mass spectrometric catalyst screening for the asymmetric Morita–Baylis–Hillman (MBH) reaction of methyl acrylate has led to the bifunctional phosphine that outperformed previously reported catalysts in terms of enantioselectivity and scope. In addition, mass spectrometric data and kinetic studies provided evidence for C−C bond formation as the enantioselectivity‐ and rate‐determining step.